Leo Nikolaevich Tolstoy and the early English Victorian novelist: William Makepeace Thackeray, Charles Dickens, Anthony Trollope and George Eliot - Buyniak, Victor (University of Ottawa (Canada), 1968)
Abstract not available.
Keywords: Literature, Comparative.; Literature, English.